Altered topological organization of brain structural network in Chinese children with developmental dyslexia. (4th March 2015) - Liu, Kai; Shi, Lin; Chen, Feiyan; Waye, Mary M.Y.; Lim, Cadmon K.P.; Cheng, Pui-wan; Luk, Sarah S.H.; Mok, Vincent C.T.; Chu, Winnie C.W.; Wang, Defeng
Highlights: We investigated the Chinese DD's brain using structural network analysis. Chinese DD's brain showed higher local specialization in topological organization. A tendency of lower E glob and prolonged characteristic path length was noted in DD. Increased regional network property was found in the left precentral gyrus. A series of Chinese-related hub regions were found unpresented in DD's network. Abstract: Increasing evidence indicates that developmental dyslexia (DD) is a "disconnection syndrome", and new probes of connectome were applied to investigate the "disconnection" in DD. However, there is a lack of brain connectome studies of Chinese dyslexics, who may have a different neural impairment pattern due to the logographic nature of Chinese. The aim of this study was to investigate the topological organization characteristics of the DD brain using a structural network based analysis on the volumetric covariance, which is a method with the advantage of reflecting brain developmental changes. Twenty-five children diagnosed with DD and twenty-five typically developing controls were included. The structural networks based on the pair-wise correlation of gray matter volume from 90 brain regions were constructed for the two groups and compared. Compared to controls, the structural network of dyslexic children exhibited significantly increased local efficiency combined with a tendency of decreased global efficiency and prolonged characteristic path length, thus reflecting a more locally specialized topological organization. Two brain areas showed significantly altered local regional network properties: the left precentral gyrus with increased bi, and the right Heschl's gyrus with decreased bi and ki . Moreover, a series of hub regions (especially the right fronto-temporal regions) identified in the network of typically developing children were not presented in the brain of DD. To our knowledge, this is the first whole-brain structural network study on Chinese dyslexics. This study provides evidence of brain topological organization changes in Chinese children with DD, and thus may help shed light on its neurobiological basis.